Marketing plan to increase LG’S TV product category premium perception by end consumers” communications plan focused on advertising - Suspiro, Eduarda Ferreira (2022)
LG Electronics is the leading brand in the Portuguese TV market, however, the brand’s premium perception among end consumers is not clear. This report develops a theoretical approach on how to leverage LG’s premium perception by advertising and communicating its premium TV lines, the LG OLED TVs. Keywords: Marketing, Integrated Marketing Communications, LG, B2C Marketing, Premium, Portugal, TV Market, Communications Plan, Advertising